2010
DOI: 10.4012/dmj.2009-137
|View full text |Cite
|
Sign up to set email alerts
|

A review of the development of radical photopolymerization initiators used for designing light-curing dental adhesives and resin composites

Abstract: This paper reviews our recent studies on radical photopolymerization initiators, which are used in the design of light-curing dental adhesives and resin composites, by collating information of related studies from original scientific papers, reviews, and patent literature. The photopolymerization reactivities of acylphosphine oxide (APO) and bisacylphosphine oxide (BAPO) derivatives, and D,L-camphorquinone (CQ)/tertiary amine were investigated, and no significant differences in degree of conversion (DC) were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
80
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(96 citation statements)
references
References 36 publications
(127 reference statements)
0
80
0
3
Order By: Relevance
“…MDP is one of the most frequently used phosphate functional monomers and was originally designed to enhance bond strength to tooth substrate and non-precious metal alloys. Similar to the interaction of phosphoric functional monomers with hydroxyapatite 15,16) , a chemical interaction is believed to occur between the functional monomer and the hydroxyl group of metal ions on the ceramic surface 17) . Kern et al 18) reported that a combination of alumina particle air abrasion and priming with MDP-containing primers provided durable, long-term bonding to dental zirconia ceramics.…”
Section: Discussionmentioning
confidence: 99%
“…MDP is one of the most frequently used phosphate functional monomers and was originally designed to enhance bond strength to tooth substrate and non-precious metal alloys. Similar to the interaction of phosphoric functional monomers with hydroxyapatite 15,16) , a chemical interaction is believed to occur between the functional monomer and the hydroxyl group of metal ions on the ceramic surface 17) . Kern et al 18) reported that a combination of alumina particle air abrasion and priming with MDP-containing primers provided durable, long-term bonding to dental zirconia ceramics.…”
Section: Discussionmentioning
confidence: 99%
“…Dental visible light curing materials generally contain a diketone-type photoinitiator that absorbs light in the 400-to 500-nm range covered by the blue light from the visible spectrum. The studies showed that the emission peak of blue LED at 465 nm coincided with the absorption peak of camphoroquinone (CQ) at 467 nm 8,15) , but when the resin material contains new photointiators that absorb light energy in lower regions of visible spectrum early generation LED lights failed when compared with QTH 16) . Interestingly, rapid cure did not have an adverse effect on Valo XP group's microleakage values.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated at about 180 teeth with a 90% confidence interval level and a standard error of 5%. Caries-free, extracted for orthodontic reasons human mandibular third molars were collected from healthy children ages [15][16][17][18][19][20]. Participants signed the informed consent form.…”
Section: Microleakage Sectionmentioning
confidence: 99%
“…Polymerization performance may change, depending on the material to be cured, as well as the light source [19]. However, there is very limited number of studies available, providing information about influence of third-generation LED LCUs on LCR.…”
Section: Introductionmentioning
confidence: 99%